The NRT2.5 and NRT2.6 genes are involved in growth promotion of Arabidopsis by the plant growth‐promoting rhizobacterium (PGPR) strain Phyllobacterium brassicacearum STM196. Issue 2 (12th February 2013) - Kechid, Maya; Desbrosses, Guilhem; Rokhsi, Wafaa; Varoquaux, Fabrice; Djekoun, Abdelhamid; Touraine, Bruno
Summary: The Phyllobacterium brassicacearum STM196 strain stimulates Arabidopsis thaliana growth and antagonizes high nitrate inhibition of lateral root development. A previous study identified two STM196‐responsive genes, NRT2.5 and NRT2.6 (Mantelin et al ., 2006, Planta 223: 591–603). We investigated the role of NRT2.5 and NRT2.6 in the plant response to STM196 using single and double Arabidopsis mutants. The single mutants were also crossed with an nrt2.1 mutant, lacking the major nitrate root transporter, to distinguish the effects of NRT2.5 and NRT2.6 from potential indirect effects of nitrate pools. The nrt2.5 and nrt2.6 mutations abolished the plant growth and root system architecture responses to STM196. The determination of nitrate content revealed that NRT2.5 and NRT2.6 do not play an important role in nitrate distribution between plant organs. Conversely, NRT2.5 and NRT2.6 appeared to play a role in the plant response independent of nitrate uptake. Using a nitrate reductase mutant, it was confirmed that the NRT2.5/NRT2.6‐dependent plant signalling pathway is independent of nitrate‐dependent regulation of root development. Our findings demonstrate that NRT2.5 and NRT2.6, which are preferentially expressed in leaves, play an essential role in plant growth promotion by the rhizospheric bacterium STM196.